Pengembangan Media Video Pembelajaran Berbasis Doratoon Pada Materi Pancasila & Pandangan Hidup Bangsa Kelas VIII SMP Negeri 3 Kabupaten Sorong - Herni Paulina Fadimpo; Indri Anugrah Rahmadhani; Sahiruddin Sahiruddin (Jurnal Kajian dan Penelitian Umum, 2024)
Various educational video media are not used at SMP Negeri 3 Sorong Regency. The objective of this study is to create educational video media based on Doratoon that is both valid, practical, and effective for instructional purposes. Employing a research and development (R&D) methodology, the study utilizes the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data gathering techniques consist of observing, conducting interviews, documenting, and employing data collection instruments. The participants in this study were 24 eighth-grade students from SMP Negeri 3 in Sorong Regency. The validation results for the development of Duratone-based educational video media were obtained through reviews by material and media experts with an average material percentage of 97% and an average media percentage of 86% meeting the "very valid" criteria. Class 8B students achieved an average of 87% in the “Very Good” category. The practicality of the teaching aids was assessed through a survey of respondents with an average score of 95.1% which indicated that it met the criteria of "very practical". The effectiveness of the media was also assessed through a survey of respondents with an average score of 95.7%, which means it is very effective to use. These findings indicate that the creation of educational video media based on Doratoon is both valid, practical, and efficient for use.